Rapid, uniform, and efficient heat transfer into dense matter using energetic proton beams with finite energy spreads. (June 2022) - Song, C.; Won, J.; Song, J.; Bang, W.
Abstract: Energetic charged particles such as laser-driven protons or ions can transfer heat into a small solid-density sample very quickly, sometimes heating it to temperatures beyond 10, 000 K. Uniform and efficient heat transfer would be desirable when measuring the physical properties of the sample after heating, but heating a thick solid-density sample both uniformly and efficiently in a short time has been very challenging. Here we show that a thick (> 1 cm) solid-density aluminum sample can be heated rapidly, uniformly, and efficiently all at the same time using an energetic proton beam with a finite energy spread. We perform Monte Carlo simulations to study the relationship between the energy spread of the incident protons and the heat transferred onto the sample for rapid, uniform, and efficient heating. We find that a 100 MeV proton beam with a Gaussian energy spread of Δ E / E 70% can transfer heat into a 32 mm thick solid-density aluminum sample uniformly (temperature nonuniformity <2–6%) and efficiently (> 62% heat transfer efficiency) on a sub-nanosecond time scale.